Factors of Cancer-Related Fatigue in Patients with Malignant Diseases - Raisa Strebkova (Journal of Biomedical & Clinical Research)
Symptoms of fatigue and exhaustion are considered to be the most common complaints in patients with oncological diseases during and after treatment. The manifestations can be on a physical, cognitive and emotional level. At diagnosis, 40% of patients report fatigue, and this percentage increases to 90% during treatment. However, the exact determinants of fatigue are not yet known. This article is a literary review of the problem of cancer-related fatigue – mechanisms, risk factors, and the impact on the lives of those affected. Literary data on the role of subjective well-being in terms of fatigue and emotional responses of patients with oncological diseases are described. A number of contemporary studies of the combined effect of fatigue and pain on the functioning of oncology patients have been discussed. It is concluded that the symptoms of fatigue, exhaustion and pain are considered the most common complaints in patients with oncologic pathology during and after treatment, whose manifestations may be physical, cognitive and emotional. On the other hand, human health satisfaction is one of the most important predictors of life satisfaction, which contributes significantly to the overall well-being of the patients group discussed.